(untitled) (African Journal of Biomedical Research, 2024)
Starches have been physically and/or chemically modified to improve their functional capacities, subsequently enhancing their use as excipients. Rice starch (Oryza sativa L. Family: Poaceae), was exposed to two-step modification and co-blended with lactose. The blends were incorporated in paracetamol formulations and evaluated for compression and release properties. Rice starch was simultaneously pregelatinized and silicified before co-blending with lactose at different ratios to obtain DMRS/L1:1, DMRS/L1:2, DMRS/L2:1. Similar blends containing unmodified rice starch and lactose (URS/L1:1, URS/L1:2, URS/L2:1) were also made. Density measurements, compressibility, surface morphology, particle size and FTIR spectroscopy were the assessment criteria for the blends, which were incorporated in paracetamol tablet formulations and evaluated for their release properties. Results were statistically evaluated using ANOVA at a significance level of p-values<0.05. Density measurements revealed higher angles of repose for the denser unmodified blends, indicating an enhancement of flow properties. DMRS/L1:2 and DMRS/L2:1 had good compressibility based on the Carr’s indices of 24.17±0.02% and 21.78±0.16% respectively. Generally, the modified powder blends were more spherical, however DMRS/L2:1 had the largest particle size (39.58±2.37µm), while URS/L1:1 had the smallest particle size (11.50±1.31µm). Modification incorporated more functional groups without compromising the basic starch integrity as observed in the FTIR plots. Tablets containing modified starches disintegrated and released the API faster, with the formulation containing DMRS/L1:2 showing the fastest release rate. Dual modification involving simultaneous pregelatinization and silicification of rice starch led to enhanced functional properties when blended with lactose and showed better tablet qualities when incorporated as excipients.